Starters experience greater weekly match and total loads than non-starters in a professional female soccer team: an exploratory analysis within the a-league women's australian competition - Lastella, M.; Elsworthy, N.; Miller, D. J.; Lundquist, M.; Serpiello, F.; Scanlan, A. T. (Sensors, 2025)
Comprehensive weekly load data appears relatively absent in the literature for the professional female soccer population. This exploratory observational study quantified the weekly training, match, and total loads experienced in a professional soccer team and compared these loads according to player role. Data were collected over a full season from 22 players competing in the Australian national A-League Women`s soccer competition. Internal (session-rating of perceived exertion load [session-RPE load]) and external load (total and relative values for total and high-speed running [HSR] distance) data were acquired during on-field training sessions and matches. Players were categorized as starters (started the match) or non-starters (used as a substitute in the match) within each week. Linear mixed models and effect size analyses were used to compare weekly loads between player roles. Weekly match and total load analyses revealed higher (p < 0.001, moderate-to-very large effects) duration, total distance, total HSR distance, and session-RPE load in starters than non-starters. In contrast, relative total and HSR distance in matches were higher (p < 0.001, moderate-to-large effects) in non-starters than in starters. These data provide an initial reference for the weekly loads in this competition, highlighting disparities between player roles that should be considered when developing training and preparation plans. Given the recruitment of a single team and small sample size, future research should extend upon this study to further strengthen the evidence base in this population.